Invasive Haemophilus influenzae Disease, Europe, 1996–2006 - Shamez Ladhani; Mary P.E. Slack; Paul T. Heath; Anne von Gottberg; Manosree Chandra; Mary E. Ramsay (Emerging Infectious Diseases, 2010)
An international collaboration was established in 1996 to monitor the impact of routine Haemophilus influenzae type b (Hib) vaccination on invasive H. influenzae disease; 14 countries routinely serotype all clinical isolates. Of the 10,081 invasive H. influenzae infections reported during 1996–2006, 4,466 (44%, incidence 0.28 infections/100,000 population) were due to noncapsulated H. influenzae (ncHi); 2,836 (28%, 0.15/100,000), to Hib; and 690 (7%, 0.036/100,000), to non–b encapsulated H. influenzae. Invasive ncHi infections occurred in older persons more often than Hib (median age 58 years vs. 5 years, p<0.0001) and were associated with higher case-fatality ratios (12% vs. 4%, p<0.0001), particularly in infants (17% vs. 3%, p<0.0001). Among non-b encapsulated H. influenzae, types f (72%) and e (21%) were responsible for almost all cases; the overall case-fatality rate was 9%. Thus, the incidence of invasive non–type b H. influenzae is now higher than that of Hib and is associated with higher case fatality.